2022
DOI: 10.1055/a-1983-6762
|View full text |Cite
|
Sign up to set email alerts
|

Peak Height Velocity Affects Injury Burden in Circa-PHV Soccer Players

Abstract: Growth and maturation are potential risk factors for soccer injuries. This research sought to describe how peak height velocity (PHV) affects overall and specific injury burden in circa- and post-PHV elite academy soccer players. Injuries and growth data collected from 2000–2020 were retrospectively studied. Longitudinal height records for 124 players were fitted with the Super-Imposition by Translation and Rotation model to calculate PHV (cm/year) and age at PHV. Players were classified according to PHV perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
(147 reference statements)
0
3
0
Order By: Relevance
“…Capturing data on a more frequent basis is, however, associated with greater variance in the estimated growth velocities 40 , and recommendations to focus on long-term tracking of anthropometric data therefore seem reasonable 33 . This approach was taken by Monasterio et al 10 15 , who calculated full growth curves. They did, unfortunately, not have individual training and match data available and growth curves could only be calculated for around 10% of their initial sample, highlighting the logistical challenges associated with accurately tracking growth, injuries, and individual exposure over a sufficient duration in applied academy settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capturing data on a more frequent basis is, however, associated with greater variance in the estimated growth velocities 40 , and recommendations to focus on long-term tracking of anthropometric data therefore seem reasonable 33 . This approach was taken by Monasterio et al 10 15 , who calculated full growth curves. They did, unfortunately, not have individual training and match data available and growth curves could only be calculated for around 10% of their initial sample, highlighting the logistical challenges associated with accurately tracking growth, injuries, and individual exposure over a sufficient duration in applied academy settings.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, a wide range in both timing (age at PHV from 12 to 17 years) and intensity (PHV from 5 to 12 cm/year) 5 6 . Studies in high-level football have indicated that phases characterized by rapid growth are associated with greater overall, overuse, acute, and non-contact injury risk 7 8 9 10 11 12 13 14 , and that players with faster PHV have a greater overall and growth-related injury burden compared to players with average or slower peak growth rates 15 . Still, it is difficult to provide clear recommendations as the associations are inconsistent and methodological differences make direct comparisons or pooling of results impossible.…”
Section: Introductionmentioning
confidence: 99%
“…21 The results of several recent studies linking higher growth rates (e.g., changes in height, leg length or body mass index) and peak height velocity have been associated with increased injury risk in high-level youth football players. [22][23][24] Injury frequency and incidence of injury were more than two times greater for males than females, as has been reported elsewhere in the ED literature.2,11,12,20 In addition to differences in social-related participation patterns, possible explanations include hormonal differences, increased joint laxity in female athletes, anatomical differences, and differences in motor control.26 However, girls tend to have higher exposure-based injury rates than boys in gender-comparable high school sports.27 Also, girls may actually be at increased risk for anterior cruciate ligament injuries in the knee28 and sport-related concussions. 29 In our study, the higher rates of injury in males were most pronounced in the 15-19 age group.…”
Section: Who Is Affected?mentioning
confidence: 99%